Financial Development and Monetary Transmission Mechanism in Nigeria (1986-2017) - Oyadeyi, Olajide; Akinbobola, Temidayo (Asian Journal of Economics and Empirical Research, 2020)
This study explored the impacts of the different aspects of financial development on monetary transmission mechanism in Nigeria from the period of 1986-2017 using quarterly data. Variables such as broad money supply, debt stock, stock market capitalization, stock market value traded, total deposit money bank’s asset, total financial assets, private sector credit, inflation rate, monetary policy rate, exchange rate, all share index and output, were used to carry out this investigation. The study adopted Pesaran, Shin, and Smith (2001) ARDL framework to check the impacts of these individual financial development indicators and how they affect monetary transmission mechanism. The findings suggested that financial development indicators and their interactions with the policy rate influenced each channel of monetary policy with different degrees. Banking sector indicators (size and activity measures) had more influence on the channels of monetary policy transmission compared to capital market indicators, while financial market liberalization had the least influence on the channels of monetary policy transmission. However, the significance of the individual financial development indicators was found to be very weak on exchange rate channel, while the influence of the financial market indicators was strongest on the interest rate channel, thereby supporting previous studies that interest rate channel is the most dominant channel of monetary policy for Nigeria. Finally, the paper recommended that financial reforms must be geared towards strengthening the implementation of monetary policy and the channels through which monetary policies impact real economic activity.